The proper analytical solution of the Korteweg-de Vries-Burgers equation - Shu, Jian Jun (2011)
On using variable transformations and proofs of theorems, the asymptotic behaviour and the proper analytical solution of the Korteweg-de Vries-Burgers equation have been found in this letter.